Effect Of Yeast Concentration (Saccharomyces cerevisiae) on Organoleptic Characteristics of Cassava Tape Local Varieties - Husain, Muhammad Faqih; Chusnah, Miftachul; Hartati, Dyah Ayu Sri; Faizah, Mazidatul (AGARICUS: Advances Agriculture Science & Farming, 2024)
Cassava is the second largest agricultural food product in Indonesia after rice One of the processed food products from cassava is tape. Cassava tape is a product resulting from a fermentation process using the yeast Saccharomyces cerevisiae as yeast. The organoleptic properties of cassava tape can change depending on the concentration of yeast used. This research aims to determine the correct yeast concentration on the organoleptic results of cassava tape. The method used in this research was the RAL method (completely randomized design) using three samples with three treatments where each treatment used 1 kg of local varieties of cassava, namely R1 with a yeast concentration of 1% (10 grams), R2 1.5% (15 grams), and R3 2% (20 grams). Another method used in this research is observation using a qualitative method approach. The data processing method used is the Analysis of Variance (ANOVA) method then the BNT test (smallest significant difference) as a further test. This research resulted in R2 cassava tape being the best-treated cassava tape with a color value of 13,13, aroma 13,26, taste 14,23, and texture 12,38. The organoleptic characteristics produced by R2 cassava tape have a slightly yellowish-white color, the characteristic aroma of cassava tape is slightly sharp, the taste is slightly sweet and slightly sour and the texture is soft. Differences in yeast concentration had a significant influence (p<0.05) on the organoleptic Characteristics of cassava tape.